New Binary Codes From Rational Function Fields - Jin, Lingfei (2015)
In this paper, we present an algebraic construction of binary codes through rational function fields. We make use of certain multiplicative group of rational functions for our construction. In particular, the point at infinity can be employed in our construction to get codes of length up to q+1, where q is the ground field size. As a result, several new binary constant-weight codes are found and many new binary nonlinear codes are presented.